Non-invasive rehabilitation in Morbus Ledderhose disease, methods, techniques, efficiency - Elena Costescu; Oana Păduraru; Gabriela Călin; Mihaiela Camelia Țabrean (Partene); Călin Ștefan Păduraru (Balneo and PRM Research Journal)
The abnormal proliferation of the fibrous tissue in the plantar fascia, Morbus Ledderhose is a non-malignant thickening of the deep connective tissue of the foot, a relatively rare pathology that intensely affects patients through marked pain and functional impotence. Rehabilitation treatments are poorly presented in the literature. To apply a non-invasive physiotherapeutic treatment which leads to consistent results in reducing pain, reducing the size of nodules or even their disappearance, the functional resumption of the foot, an increase in the life quality of affected patients. In the study, patients were divided into 2 groups: G1 received treatment consisting of shockwave therapy complemented with SIS therapy, G2 received treatment consisting of ultrasound, laser therapy, kinesiotherapy, massage, excluding the application of shockwave therapy and SIS. Some of the patients associate comorbidities such as type II diabetes, Dupuytren’s disease or, more rarely, with Peyronie’s disease (penile fibromatosis). Important positive results have been obtained: a considerable decrease in the pain level of patients, the dissipation of consistency and decrease in the size of plantar nodules, an increase in the life quality of the patients with the resumption of productive activities. The treatment with shock waves and super inductive system has an increased efficiency both folowing the first cure and after various consecutive cures applied consistently at 6 months or maybe even faster, at 4-5 months, if necessary, if the pathology advances faster by intensifying fibrosis